A study on customer satisfaction on internet services provided by Telekom Malaysia Berhad at Kuala Terengganu Branch / Suriani Mohamad @ Khalid - Mohamad @ Khalid, Suriani (2002)
The use of Internet technologies is leading to a dramatic change either for personal use or for business purpose. People are increasingly acknowledging the importance of Internet to enhance communication. The number of Internet subscribers are larger at an increasing rate especially after TMnet was introduced and launched its service. The aim of this study is to identify the level of customer satisfaction on Internet services provided by Telekom Malaysia Berhad at Kuala Terengganu Branch. Satisfaction for these services actually will be measure in term quality of service, benefit and price. This report will outline the findings, analysis and recommendation based on the set of questionnaires distributed to the customer. If we look overall, to measure customer satisfaction is one of difficult jobs for all of the company. It is happened because satisfaction is subjective in meaning and different customers have different perception and opinion.